Attenberg [videorecording (DVD)] - Tsangari, Athina Rachel; Labed, Ariane; Mourikis, Vangelis; Randou, Evangelia (Strand Releasing Home Video, 2012)
A wonderfully deadpan, surprisingly touching coming-of-age story. 23-year-old Marina lives in a small, factory town by the sea where she passes her time watching Sir David Attenborough's nature programs, listening to the proto-punk songs of Suicide, goofing with her only friend Bella, and tending to her ailing father. When a visiting engineer comes to town, the two form a tentative relationship that pushes Marina into contact with the strange and complex world of adulthood.